HyperForm Balloon-Assisted Endovascular Neck Bypass Technique to Perform Balloon or Stent-Assisted Treatment of Cerebral Aneurysms - Cekirge, S.H. (AJNR Am J Neuroradiol, 2007)
SUMMARY: We describe a technique to bypass aneurysm neck using the HyperForm balloon to perform balloon- or stent-assisted endovascular treatment of complex large or giant aneurysms with very wide neck in which other methods would fail to obtain an access distal to the aneurysm.